Peran Viral Marketing sebagai Strategi Pemasaran melalui Media Sosial Tiktok Persfektif Islam - Lestari Perdana Putri; Zuhrinal M. Nawawi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Viral marketing is a marketing activity carried out via the internet, with virtual of mouth spreading information to the internet community. The reach of viral marketing is very wide to various countries with low costs. One of the internet marketing is through social media tiktok, because millennials spend a lot of time on tiktok, this is used by companies or businesses. This study uses qualitative research, with secondary data or previous research data relevant to this study. The purpose of this study is to determine the role of viral marketing as a social media marketing strategy for Tiktok from an Islamic perspective. The results of the study show that the viral marketing strategy as marketing is very effective because it is very minimal in cost and time, unlike other marketing. Viral marketing can also be done in Islam.